Artemis Fowl. The Atlantis complex - Colfer, Eoin (Colfer, Eoin. Artemis Fowl, 2010)
Teenaged criminal mastermind Artemis Fowl must save the underwater fairy metropolis of Atlantis from danger, while battling a psychological affliction known as the Atlantis Complex.